2022
DOI: 10.3390/biology11020192
|View full text |Cite
|
Sign up to set email alerts
|

Homogenisation of Biocultural Diversity: Plant Ethnomedicine and Its Diachronic Change in Setomaa and Võromaa, Estonia, in the Last Century

Abstract: When studying the evolution of the use of medicinal plants, it is important to identify what role, and to what extent, external factors and local biocultural diversities play in shaping cultural changes. We chose as a case study, which forms part of a larger project, a religiously and linguistically distinct group, the Seto, and compared their current and past plant use with that of the surrounding Võro. Ethnobotanical fieldwork was conducted in the summers of 2018 and 2019. Current uses of plants constituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
2
18
1
4
Order By: Relevance
“…Specific plant spices and their combinations play key roles in the local cuisines that underline their uniqueness [67][68][69]. Practicing of traditional (agro)ecological knowledge is of crucial importance, as demographic and socioeconomic changes in the rural areas, especially in industrialized societies, gradually diminish natural human connectedness [4,70,71]. While utilization of M. spicata was reported from all over the world [29,[72][73][74], S. hortensis was found popular both as a culinary herb and a medicinal plant mainly in the Balkans, Iran, and Turkey [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Specific plant spices and their combinations play key roles in the local cuisines that underline their uniqueness [67][68][69]. Practicing of traditional (agro)ecological knowledge is of crucial importance, as demographic and socioeconomic changes in the rural areas, especially in industrialized societies, gradually diminish natural human connectedness [4,70,71]. While utilization of M. spicata was reported from all over the world [29,[72][73][74], S. hortensis was found popular both as a culinary herb and a medicinal plant mainly in the Balkans, Iran, and Turkey [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings have shown that the local communities that have remained in close contact with nature have maintained considerable peculiarities regarding plant foraging (e.g. Mattalia et al, 2021 ), although in Estonia foraging practices are fading away within the lifetime of one generation due to changes in land management and social changes (Kalle & Sõukand, 2016 ; Kalle et al, 2020 ; Sõukand et al, 2022 ). However, there still exists a remarkable store of traditional/local environmental knowledge (TEK) on foraging, as recorded in each of the case studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, we mainly rely on unpublished qualitative data arising from several previous ethnobotanical case studies devoted to recording plant-related foraging practices that were conducted in coastal Syria (Sulaiman et al, 2022 ), Eastern Europe (Kalle, 2017 ; Kalle & Sõukand, 2016 ; Pieroni & Sõukand, 2017 , 2018 ; Mattalia et al, 2020 , 2021 ; Sõukand, 2016 ; Sõukand & Kalle, 2016 ; Sõukand & Pieroni, 2016; Stryamets et al, 2021 ; Sõukand et al, 2022 ), and North Pakistan (Aziz et al, 2020a , b , 2021a , b ), representing three different human ecological environments as described in Table 1 .…”
Section: Study Areas and Methodologymentioning
confidence: 99%
“…On the other hand, the indigenous culture formed around native organisms, such as traditional ecological concepts and village rules and regulations, restricts local people from damaging the environment and endangering local organisms [ 57 , 58 ]. The biodiversity of indigenous areas is positively correlated with the cultural diversity of indigenous peoples [ 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%